2011
DOI: 10.1111/j.1444-0938.2010.00563.x
|View full text |Cite
|
Sign up to set email alerts
|

Refractive errors in students from Middle Eastern backgrounds living and undertaking schooling in Australia

Abstract: Background:  Environmental factors associated with schooling systems in various countries have been implicated in the rising prevalence of myopia, making the comparison of prevalence of refractive errors in migrant populations of interest. This study aims to determine the prevalence of refractive errors in children of Middle Eastern descent, raised and living in urban Australia but actively maintaining strong ties to their ethnic culture, and to compare them with those in the Middle East where myopia prevalenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
2
13
0
Order By: Relevance
“…Although poor living conditions and low SES increase the chance of respiratory tract infections [ 35 ], the self-reported incidence of colds among migrant children was not significantly higher than among permanent resident children, which is a manifestation of migrant paradox. Second, the prevalence of overweight and obesity and prevalence of poor vision among migrant children were lower than those in permanent resident children, which appears to demonstrate the migrant paradox phenomenon, and is also consistent with studies on adolescent health among international migrants [ 5 , 36 , 37 ]. However, the phenomenon of better health than native children is consistent with the relatively low SES of migrant children.…”
Section: Discussionsupporting
confidence: 86%
“…Although poor living conditions and low SES increase the chance of respiratory tract infections [ 35 ], the self-reported incidence of colds among migrant children was not significantly higher than among permanent resident children, which is a manifestation of migrant paradox. Second, the prevalence of overweight and obesity and prevalence of poor vision among migrant children were lower than those in permanent resident children, which appears to demonstrate the migrant paradox phenomenon, and is also consistent with studies on adolescent health among international migrants [ 5 , 36 , 37 ]. However, the phenomenon of better health than native children is consistent with the relatively low SES of migrant children.…”
Section: Discussionsupporting
confidence: 86%
“…In an earlier study we have demonstrated that the refractive distribution for children of Middle Eastern background but residing and being educated in Australia, is similar to the known Australian norms for Caucasians [ 15 ]. Such results implicate educational style, especially years of schooling and associated near work (see review [ 13 ]), as significant environmental influences in the development of refractive error [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 71%
“…13,33 The prevalence of myopia across populations of different regions is shown in Table 6. [18][19][20]27,[34][35][36][37][38][39][40] There are three possible explanations for our high myopia prevalence. First, screening was performed in schools in the urban areas of Turkey.…”
Section: Discussionmentioning
confidence: 99%